SISTEM INFORMASI JEJARING SOSIAL DAN FORUM DISKUSI BERBASIS PHP : SISTEM INFORMASI JEJARING SOSIAL DAN FORUM DISKUSI BERBASIS PHP - Ari Purno Wahyu; Taufik Hidayat (Universitas Widyatama, 2022)
The rapid advancement of technology in the field of information has encouraged the emergence of social networking sites. Sites that have many interesting features and can be easily accessed and applied by all circles of society. Distance becomes meaningless, differences become the reason for unity for every participating person, including a discussion forum site that is useful for showing the existence of the community or organization. Currently the BALMON office has a very wide range to support things that are not possible to carry out. Maintenance and coordination meetings make it impossible to do every day, therefore BALMON requires a social networking facility so php social networking system was created. Balmon Forum information can be used as a means of communication between members or Balmon Staff.